Walking into the cyborg gym. Two conceptions of the cyborg athlete - Lopez Frías, Francisco Javier (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2018)
In this paper, I will draw on the different notions of the cyborg to explore the normative implications of technology use in sport. To do so, I will first analyze the colloquial notion of the cyborg (Section 1). Then, I will differentiate between transhuman cyborgs, which are enhanced human beings who keep their defining human characteristics intact from the impact of technology, from posthuman cyborgs, which are beings whose involvement with technology blurs the line between what is human and what is not (Section 2). By applying the transhuman/posthuman distinction to sport, I will differentiate transhuman sport from posthuman sport. These two notions of sport will provide the basis for analyzing two conceptions of the cyborg-athlete: the transhuman cyborg-athlete and the posthuman one (Section 3). To conclude, I will identify the transhuman cyborg-athlete as the prevailing notion of the cyborg in contemporary sports and will present the main normative challenges that each conception of the cyborg-athlete raises.